FEATURES OF THE ORGANIZATION OF MARKETING ACTIVITIES ON TV (Conferencea, 2022)
A significant impact on the competitiveness of TV channels is exerted by its marketing activities, which determine the possibilities for the implementation and promotion of television services. Marketing is indispensable in the local environment of TV channels due to the growing competition in the television services market, the emergence of new broadcast formats that offer viewers and advertisers a wide range of TV products. At the same time, a consequence of the development of marketing activities in the television environment was the development of audience preferences, which arose in the process of providing the advertiser with an information base about the target audience of the media, including TV channels.